The making of local public sphere: case studies in Kebumen regency and Batu City in Central and East Java - Putra, I Gusti Ngurah (Penerbit Universiti Kebangsaan Malaysia, 2020)
Studies on democracy in Indonesia focus mainly on aspects related to the basic characteristics of democracy such as the existence of elite circulation through elections that allow everyone to hold power through a democratic process, the existence of political parties as instruments in political recruitment and aspects of procedural democracy and other institutional aspects. This study, in line with the spirit of democratisation in Indonesia, coupled with regional autonomy, focused on the formation of a public sphere in the transition to democracy at the local level by using the Kebumen Regency and Batu City as the main cases. The selection of these two regions was based on the consideration of the awareness of local elites in both regions to create the public sphere by establishing TV broadcasting stations that theoretically could reach the majority of citizens and involve citizens to discuss a wide range of common issues they face. The paper was based on a research conducted in the two regions using a case study approach. The research employed two main methods, namely in-depth interviews with informants involved in the establishment and management of the media (Ratih TV Kebumen and Agropolitan TV in Batu City) and used documents on the establishment and management of the two TV stations.